Pendampingan UMKM (Usaha Mikro Kecil Menengah) Dengan Pelatihan Digital Marketing Di Desa Kalibaru Manis - Nurul Inayah; Abdul Kholiq Syafa'at; Yunus Zamroji; Ahmad Said Naja (LOYALITAS: Jurnal Pengabdian Kepada Masyarakat, 2022)
Business actors are slowly starting to leave conventional marketing methods and switch to digital marketing. Digital marketing is the marketing of products or services using digital technology via the internet, social media, cell phones, or other digital media. There are many advantages to getting from digital marketing, namely: scalable, more efficient, and broad-reaching. With the application of digital marketing, it is hoped that MSME actors will be able to develop and compete. MSME owners in Kalibaru Manis village still have problems such as limited human resources, limited business capital, system limitations in business administration, and the lack of ability for marketing, especially promotion, making them less able to compete with large business owners who are already strong and supported by advanced technology. advanced. Then, UMKM (Micro, Small, and Medium Enterprises) assistance was carried out with Digital Marketing training in Kalibaru Manis Village, Banyuwangi Regency. With digital marketing training, it is hoped that it will be able to develop the business sector for MSME actors in Kalibaru Manis village. With collaboration with youth organizations, we are able to preserve the program that we run while carrying out mentoring in the village of Kalibaru Manis.